Analysis of Arabic Textbook for Grade X of ISMUBA Curriculum (2017) in The Perspective of Rushdi Ahmad Thu'aimah - Kabalmay, Taqiyuddin; Muhaiban, Muhaiban; Khasyitullah, Zaki (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the suitability of Arabic teaching materials based on Rusydhi Ahmad Thu'aimah’s perspective, focusing on four key aspects: content, material organization, presentation, and appearance. Employing a non-interactive qualitative approach, this research relies on document analysis. Data were collected through content analysis procedures, including data gathering, conclusion drawing, and verification. The primary data source is the Arabic language textbook for Grade X used in the 2017 ISMUBA curriculum. The findings reveal that, in terms of content, the material aligns with learning objectives, follows a systematic structure, and integrates the four basic language skills. Regarding organization, the book comprises six chapters and thirty subchapters that cover daily themes, supported by illustrations, vocabulary lists, grammar explanations, and practice exercises that enhance comprehension and language application. In terms of presentation, the textbook features an appealing cover design, a readable layout, and contextual illustrations that facilitate effective learning. Overall, the textbook demonstrates high quality in content, organization, presentation, and visual design, making it a suitable resource for Arabic language instruction at the high school level, in line with Thu’aimah’s criteria.